Determinants of job satisfaction among employees at the Ministry of Religious Affairs Office in Palembang - Felya, Finka; Mursalin, Mursalin; Heryati, Heryati (Global Academy of Business Studies, 2024)
Purpose: This study aims to examine the influence of competence, independence, and professionalism of government internal auditors on audit quality at the Representative Office of the Financial and Development Supervisory Agency (BPKP) in South Sulawesi Province. Research methodology: The study involved 40 respondents selected through random sampling from all internal auditors at the BPKP Representative Office. A quantitative approach was applied using primary data collected through questionnaires. Data were analyzed using descriptive statistics, normality and linearity tests, multicollinearity, heteroscedasticity, multiple regression, R Square, t-tests, and F-tests. Results: The findings indicate that competence and professionalism significantly and positively affect audit quality, whereas independence has a positive but insignificant effect. Simultaneously, competence, independence, and professionalism collectively have a positive and significant impact on audit quality at BPKP South Sulawesi. Conclusion: Audit quality is largely determined by competence and professionalism, highlighting the importance of expertise and professional standards in ensuring effective supervision. Independence alone is insufficient without strong competence and professionalism. Limitation: The research was limited to a small sample size within a single regional office, which may restrict its generalizability. Broader studies across multiple regions and larger populations are therefore recommended. Contribution: This study enriches the public sector auditing literature by highlighting the mediating role of competence and professionalism. Practically, it guides policymakers and BPKP to strengthen training, continuous professional development, and auditing standards to enhance accountability and effectiveness.